Mint leaf extract (Mentha x piperita L.) and Bay Leaves (Syzygium polyanthum (Wight) Walp.) As Additional Ingredients for Making Hand Sanitizer - Winandari, Ovi Prasetya; Anisya, Shinta; Carolin, Lili Anisa (Biology, Medicine, & Natural Product Chemistry, 2025)
Spray Hand Sanitizer In this study is a product used as an alternative hand cleansing with the addition of mint leaf extract and bay leaves that contain secondary metabolitic compounds and can form an antibacterial inhibitory zone. This study aims to determine the effectiveness of the addition of mint leaf extract (Mentha x piperita L.) and bay leaves (Syzygium polyanthum (Wight.) Walp.) As a spray hand sanitizer formulation. The method used is quantitative with a complete random design research design (RAL) consisting of 4 treatments, namely: P0 (30% Bay leaf extract: Control), P1 (3% Mint Leaf Extract + 30% Salam Leaf Extract), P2 (5 % Mint leaf extract + 30% bay leaf extract) and P3 (7% mint leaf extract and 30% bay leaf extract). Data analysis techniques in the form of ANOVA tests and further DMRT tests. The results showed that the addition of mint leaf extract and bay leaves gave effectiveness to the hand sanitizer formulation with the ability to form an inhibitory zone for the staphylococcus aureus bacteria. The largest inhibitory zone is formed by the P3 formulation with an average diameter of 15.78 mm category of strong inhibition. The spray hand sanitizer formulation that is preferred by panelists is the P3 formulation (7% of mint leaf extract + 30% bay leaf extract). The average value of the P3 formulation in the color parameter of 3.57, the aroma parameter of 3.63, the parameter of the use of 3.4 and the absorption rate of 3.57 with a fairly like category.